PENGARUH MOTIVASI DALAM BENTUK PEMBERIAN BONUS TERHADAP PRODUKTIVITAS KARYAWAN BAGIAN KREDIT PT BANK RAKYAT INDONESIA (PERSERO) CABANG TOBELO - Hernansi Biso; Jerrivan Ova (http://jurnal.untirta.ac.id/index.php/JIPAGS, 2019)
The rapid development of the banking world requires existing banks to obtain quality human resources, to produce the expected human resources. One way to do this is to motivate human resources appropriately, including Bank Rakyat Indonesia, which provides bonuses to employees who provide productivity. good at work. Provision of bonuses given by the People's Bank of Indonesia to employees is based on the amount of funds collected by each employee. So that it can motivate employees to give their best productivity at work. Based on the measurement of employee productivity from 2012-2016, the results show that every year there is an increase in employee productivity at Bank Rakyat Indonesia. And the results of the regression analysis showed that the value of t arithmetic was 5.992> t table 3.182, so HO was processed and ha was received so that there was an effect of giving bonuses to the work productivity of Bank Rakyat Indonesia employees. 2.5% is influenced by other factors. Keywords: Motivation, giving bonuses, productivity, employees